Pengujian Fungsionalitas Aplikasi Peminjaman Ruang Kelas Berbasis Web (Pinjam Kelas Web-App) Menggunakan Metode Blackbox Testing - Ria Anhar; Shantika Dwi Kurniawati; Muhamad Syahid; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
The manual classroom borrowing mechanism often causes problems in terms of efficiency and accountability due to its reliance on paper usage. To address this, the Pinjam Kelas Web-App was developed as a PHP-based classroom borrowing system that allows borrowing applications and management to be conducted digitally. This testing aims to evaluate the functionality and integration of the Pinjam Kelas Web-App system. Functionality testing includes main features such as borrowing applications, borrowing management (including approval, deletion, and data checking), as well as downloading borrowing data based on dates. Meanwhile, integration testing emphasizes the application's ability to interact with a prototype of a simple automatic door locking hardware using RFID and Solenoid Door Lock, which is an innovation in the classroom borrowing system. The responsiveness aspect of the web design is also tested to ensure that the user interface adapts well to various devices, both computers and mobile phones. The test results show that the Pinjam Kelas Web-App operates according to the specified specifications, thus providing an effective, efficient, and integrated alternative to replace the manual classroom borrowing procedures.